Effects of vanadium and cadmium on transformation temperatures of Cu-Al-Mn shape memory alloy - Canbay, C. Aksu; Keskin, A. (Springer, 2014)
Cu-based quaternary shape memory alloys were extensively investigated alloy in last decade. In this study, Cu-Al-Mn, Cu-Al-Mn-V and Cu-Al-Mn-Cd shape memory alloys were produced by arc melting. We have investigated the effects of the alloying elements on the characteristic transformation temperatures, variations in structure and microstructure. The characterization of the transformation temperatures was studied by the differential scanning calorimetry. It was observed that the addition of the vanadium and cadmium decreases the characteristic transformation temperatures. The structural changes of the samples were studied by X-ray diffraction measurements and optical microscope observations. The crystal structure of the martensite Cu-Al-Mn, Cu-Al-Mn-V and Cu-Al-Mn-Cd shape memory alloys were identified as M18 at room temperature. The crystallite sizes of the alloys were determined. The microstructure of the alloy was studied with the help of optical microscope and V-type martensites with different orientations were detected. Microhardness value of the alloys were found between 194 and 211 Hv.
Keywords: CuAlMnV; CuAlMnCd; Shape memory alloys; Thermal analysis; Structural analysis